Maternal HLA Ib Polymorphisms in Pregnancy Allo-Immunization - Persson, Gry; Picard, Christophe; Marin, Gregory; Isgaard, Cecilie; Stæhr, Christina Seefeldt; Molinari, Nicolas; Chiaroni, Jacques; Lebech, Morten; Hviid, Thomas Vauvert F.; Di Cristofaro, Julie (Frontiers in Immunology, 2021)
During pregnancy the formation of alloreactive anti-human leukocyte antigen (HLA) antibodies are a major cause of acute rejection in organ transplantation and of adverse effects in blood transfusion. The purpose of the study was to identify maternal HLA class Ib genetic factors associated with anti-HLA allo-immunization in pregnancy and the degree of tolerance estimated by IgG4 expression. In total, 86 primiparous women with singleton pregnancies were included in the study. Maternal blood samples and umbilical cord samples were collected at delivery. Clinical data were obtained. Maternal blood serum was screened for HLA class I and II antibodies, identification of Donor Specific Antibody (DSA), activation of complement measured by C1q, and IgG4 concentrations. Mothers were genotyped for HLA class Ib (HLA-E, -F and -G). Anti-HLA class I and II antibodies were identified in 24% of the women. The maternal HLA-E*01:06 allele was significantly associated with a higher fraction of anti-HLA I immunization (20.0% vs. 4.8%, p = 0.048). The maternal HLA-G 3’-untranslated region UTR4-HLA-G*01:01:01:05 haplotype and the HLA-F*01:03:01 allele were significantly associated with a low anti-HLA I C1q activation and a high IgG4 expression (16.7% vs. 57.1%, p = 0.028; 16.7% vs. 50.0%, p = 0.046; respectively). Both HLA G UTR4 and HLA-F*01:03:01 showed significantly higher levels of IgG4 compared with the other haplotypes. The results support an association of certain HLA class Ib alleles with allo-immunization during pregnancy. Further studies are needed to elucidate the roles of HLA-E*01:06, HLA-F*01:03 and HLA G UTR4 in reducing the risk for allo-immunization.